Analysis of new haddul kifayah on income zakat in Kedah state - Abd Muin, Mohd Adib; Shuib, Mohd Sollehudin; Che Omar, Azizah (2019)
This study focuses on the new rate of haddul kifayah on income zakat in the state of Kedah. Lembaza Zakat Negeri Kedah (LZNK) are responsible to determine the limits of haddul kifayah zakat especially on the income zakat for Kedah state. The rate of haddul kifayah is a measure of the adequacy of the individual to incur expenses for the basic needs of the person and the member under his dependence for basic life. The haddul kifayah method in income zakat is currently based on the estimated income tax from the Inland Revenue Board (IRB) and the Poverty Line Income (PGK) issued by the Department of Statistics, Malaysia. Since the current economic level is so high with various costs and prices rising, the study of the effect of new haddul kifayah in zakat income needs to be done so that this re-examination can attract more paying zakat payers. Hence, the objective of this study is to analysis of new haddul kifayah on income zakat in Kedah. The methods for this study are qualitative method, comparative analysis, library method and the analysis of the contents of the previous studies and refers to the Qur'an and Hadith. The findings of this study show that there are some implications that occur when the new haddul kifayah is implemented. Therefore, scientific discussions will be discussed in this paper.